Computer security fundamentals - Easttom, Chuck ([Indianapolis, Indiana] : Pearson Education, Inc., 2019)
"[This book] explains core concepts, terminology, challenges, technologies, and skills; covers today's latest attacks and countermeasures ... Chuck Easttom brings together complete coverage of all basic concepts, terminology, and issues, along with all the skills students need to get started. Drawing on 20+ years of experience as a security instructor, consultant, and researcher, Easttom helps students take a proactive, realistic approach to assessing threats and implementing countermeasures. Writing clearly and simply, he addresses crucial issues that many introductory security books ignore, while addressing the realities of a world where billions of new devices are Internet-connected. This guide covers web attacks, hacking, spyware, network defense, security appliances, VPNs [virtual private networks], password use, and much more. Its many tips and examples reflect new industry trends and the state-of-the-art in both attacks and defense. Exercises, projects, and review questions in every chapter help students deepen their understanding and apply all they've learned. Whether you're a student, a professional, or a manager, this guide will help you protect your assets, and expand your career options"--Provided by the publisher.
Introduction to Computer Security -- Networks and the Internet -- Cyber Stalking, Fraud and Abuse -- Denial of Service Attacks -- Malware -- Techniques used by Hackers -- Industrial Espionage in Cyberspace -- Encryption -- Computer Security Software -- Security Policies -- Network Scanning and Vulnerability Scanning -- Cyber Terrorism and Information Warfare -- Cyber Detective -- Introduction to Forensics -- Cybersecurity Engineering
Place of publication taken from the publisher's website.
Previous edition: Indianapolis : Pearson, 2016.
Includes bibliographical references and index.
Keywords: Computer security; Computer networks -- Security measures; Evidence, Criminal